Agreement in Left Ventricular Function Measured by Echocardiography and Cardiac Magnetic Resonance in Patients With Chronic Coronary Total Occlusion - Li, Jiahui; Zhang, Lijun; Wang, Yueli; Zuo, Huijuan; Huang, Rongchong; Yang, Xueyao; Han, Ye; He, Yi; Song, Xiantao (Frontiers in Cardiovascular Medicine, 2021)
Aims: To determine the agreement between two-dimensional transthoracic echocardiography (2DTTE) and cardiovascular magnetic resonance (CMR) in left ventricular (LV) function (including end-systolic volume (LVESV), end-diastolic volume (LVEDV), and ejection fraction (LVEF)) in CTO patients. Methods: Eighty-eight CTO patients were enrolled in this study. All patients underwent 2DTTE and CMR within one week. The correlation and agreement of LVEF, LVESV and LVEDV as measured by 2DTTE and CMR were assessed using Pearson correlation, Kappa analysis and Bland-Altman method. Results: The mean age of patients enrolled was 57 ± 10 years. There was a strong correlation (r=0.71, 0.90 and 0.80, respectively, all P<0.001) and a moderately strong agreement (Kappa=0.62, P<0.001) between the two modalities in measurement of LV function. The agreement in patients with EF≧50% was better than in those with an EF <50%. CTO patients without echocardiographic WMA had stronger intermodality correlations (r=0.84, 0.96, and 0.87, respectively) and smaller biases in LV function measurement. Conclusions: The difference in measurement between 2DTTE and CMR should be noticed in CTO patients with EF<50% or abnormal ventricular motion. CMR should be considered in these conditions.